Effect of impurities on the microhardness of borax decahydrate - KIRAN YILDIRIM, BERÇEM; SAYAN, PERVİZ; SARGUT, SİBEL (ELSEVIER, 2010)
Microhardness of borax decahydrate single crystals grown from pure and impure borax solutions was measured. It was found that the microhardness of borax decahydrate crystals showed clear load dependence. The results obtained from Meyer Law indicated that Meyer index was found to be less than 2. The microhardness measurements were also evaluated according to the PSR (proportional specimen resistance) model to analyze normal ISE and measured microhardness values were converted to load-independent microhardness. The variation of these load independent microhardness values with different types and concentrations of impurities was determined and found that the microhardness of borax decahydrate crystals was strongly affected by ionic impurities. Based on microhardness measurements it was observed that radial and lateral cracks occurred during the measurements. The dependence of these crack lengths on applied load and fracture toughness was investigated by some empirical equations. Crystal surface stresses were evaluated using an empirical equation and it was determined that tensile stresses were effective on the microhardness of borax decahydrate crystals. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Borax decahydrate; Ionic impurities; Microhardness; Indentation size effect (ISE); Fracture toughness; CRYSTALLIZATION PROCESSES; IMPACT ATTRITION; CRYSTALS